Limits of (Im)Mortality - Reflections on the Right to Die in the Context of the Transhumanist Vision of the Future Human - Nowak-Gruca Aleksandra (Medicine, Law & Society, 2022)
Contemporary breakthrough discoveries of biological sciences and the ongoing technological revolution make the problem of the border of human life and the ways of its designing sound today in a completely new light. The aim of the paper is primarily to identify problems that arise on the legal grounds in connection with the latest discoveries of science. There is doubt as to whether dynamically developing social movements, such as transhumanism, do not require rethinking, in a completely new context, the right to death, subject to the huge complexity of this issue. The paper points out that in the light of immortality projects, there is the need to regulate the right to death in a manner significantly different from the already existing and still controversial approaches. The considerations carried out in the article are futurological and legal in nature, but it was mainly about a panoramic overview of legal problems related to biotechnological progress and projects of extending human life, including up to eternity.